What Price Parenthood? - Lauritzen, Paul (The Hastings Center report, 1990)
Current reproductive technology challenges us to think seriously about social values surrounding childbearing. Thoughtful discussion must combine careful attention to the experience of pursuing parenthood by technological means with principled reflection on the morality of this pursuit.